Congruency of body-related information induces somatosensory reorganization. (April 2016) - Cardini, Flavia; Longo, Matthew R.
Abstract: Chronic pain and impaired tactile sensitivity are frequently associated with "blurred" representations in the somatosensory cortex. The factors that produce such somatosensory blurring, however, remain poorly understood. We manipulated visuo-tactile congruence to investigate its role in promoting somatosensory reorganization. To this aim we used the mirror box illusion that produced in participants the subjective feeling of looking directly at their left hand, though they were seeing the reflection of their right hand. Simultaneous touches were applied to the middle or ring finger of each hand. In one session, the same fingers were touched (for example both middle fingers), producing a congruent percept; in the other session different fingers were touched, producing an incongruent percept. In the somatosensory system, suppressive interactions between adjacent stimuli are an index of intracortical inhibitory function. After each congruent and incongruent session, we recorded somatosensory evoked potential (SEPs) elicited by electrocutaneous stimulation of the left ring and middle fingers, either individually or simultaneously. A somatosensory suppression index (SSI) was calculated as the difference in amplitude between the sum of potentials evoked by the two individually stimulated fingers and the potentials evoked by simultaneous stimulation of both fingers. This SSI can be taken as an index of the strength of inhibitory interactions and consequently can provide a measure of how distinct the representations of the two fingers are. Results showed stronger SSI in the P100 component after congruent than incongruent stimulation, suggesting the key role of congruent sensory information about the body in inducing somatosensory reorganization. Highlights: Somatosensation is strongly linked with cortical representations of the body. Factors inducing somatosensory organization are poorly understood. Congruency in body-related inputs affects somatosensory reorganization. Effects of congruency are observed in the P100 SEP component.